How important is the choice of the nutrient profile model used to regulate broadcast advertising of foods to children? A comparison using a targeted data set. - Scarborough, P; Payne, C; Agu, C; Kaur, A; Mizdrak, A; Rayner, M; Halford, J; Boyland, E (2013)
BACKGROUND/OBJECTIVE: The World Health Assembly recommends that children's exposure to marketing of unhealthy foods should be reduced. Nutrient profile models have been developed that define 'unhealthy' to support regulation of broadcast advertising of foods to children. The level of agreement between these models is not clear. The objective of this study was to measure the agreement between eight nutrient profile models that have been proposed for the regulation of marketing to children over (a) how many and (b) what kind of foods should be permitted to be advertised during television viewed by children. SUBJECTS/METHODS: A representative data set of commercials for foods broadcast during television viewed by children in the UK was collected in 2008. The data set consisted of 11,763 commercials for 336 different products or brands. This data set was supplemented with nutrition data from company web sites, food packaging and a food composition table, and the nutrient profile models were applied. RESULTS: The percentage of commercials that would be permitted by the different nutrient profile models ranged from 2.1% (0.4%, 3.7%) to 47.4% (42.1%, 52.6%). Half of the pairwise comparisons between models yielded kappa statistics less than 0.2, indicating that there was little agreement between models. CONCLUSIONS: Policy makers considering the regulation of broadcast advertising to children should carefully consider the choice of nutrient profile model to support the regulation, as this choice will have considerable influence on the outcome of the regulation.